DESICCATION TOLERANCE AND OSMOTIC PARAMETERS IN DETACHED LEAVES OF QUERCUS-ILEX L - KYRIAKOPOULOS, E; RICHTER, H (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1991)
Batches of detached Quercus ilex leaves from a natural site were desiccated to different relative water contents. The percentage of necrotic leaf area was evaluated after resaturation, and necrosis of 1-2% defined as ``incipient injury{''}. The relative water content at incipient injury was higher in the dry summer than in the humid winter. Osmotic potentials of young leaves decline rapidly during leaf maturation; the values are not closely coupled to desiccation tolerance. The results are discussed with reference to the evolutionary origins of Quercus ilex, an Arcto-Tertiary element of the Mediterranean flora.
Keywords: DESICCATION TOLERANCE; OSMOTIC PARAMETERS; QUERCUS-ILEX